2014
DOI: 10.1371/journal.pone.0112645
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microRNA Expression Profiles in Mouse Renal Cortical Tissue after 177Lu-octreotate Administration

Abstract: AimThe aim of this study was to investigate the variation of the miRNA expression levels in normal renal cortical tissue after 177Lu-octreotate administration, a radiopharmaceutical used for treatment of neuroendocrine cancers.MethodsFemale BALB/c nude mice were i.v. injected with 1.3, 3.6, 14, 45, or 140 MBq 177Lu-octreotate, while control animals received saline. The animals were killed at 24 h after injection and total RNA, including miRNA, was extracted from the renal cortical tissue and hybridized to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…As previously described, its expression significantly increased in patients responding to preoperative chemoradiotherapy in advanced rectal cancer [20]. Indeed, it is likely that miR-194 expression can depend on radiation doses (7 Gy in our experiments), since it is already known to be regulated at high absorbed doses used for the treatment of neuroendocrine cancers [21]. The expression of miR-194 is clearly correlated with a tumor suppressor function in various cancers including hepatocarcinoma in which it regulates PTBP1 expression involved in tumor proliferation and migration, but also in glioblastoma [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…As previously described, its expression significantly increased in patients responding to preoperative chemoradiotherapy in advanced rectal cancer [20]. Indeed, it is likely that miR-194 expression can depend on radiation doses (7 Gy in our experiments), since it is already known to be regulated at high absorbed doses used for the treatment of neuroendocrine cancers [21]. The expression of miR-194 is clearly correlated with a tumor suppressor function in various cancers including hepatocarcinoma in which it regulates PTBP1 expression involved in tumor proliferation and migration, but also in glioblastoma [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…Increased expression of miR-1949 was previously shown in injured kidney tissue in a rat model of deep hypothermic circulatory arrest [ 49 ]. Previous research demonstrated increased expression of miR-3084-3p in the renal cortices of mice treated with 177 Lu-octreotate, and this radionuclide therapy used for treating neuroendocrine tumors is known to cause renal toxicity at the level of the proximal tubule [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR107 is overexpressed in mouse renal cortical tissue after administration of 177 Lu-octreotate, which is a radiopharmaceutical used for treatment of neuroendocrine cancers. 103 However, a recent study found that long-term and excessive use of 900 MHz radiofrequency radiation downregulated rno-miR107 expression in Wistar albino adult male rat brains. 104 …”
Section: Factors Influencing Mir107 Expression In Cancer Cell Linesmentioning
confidence: 97%